Implementasi akad ijarah pada jasa event organizer project 13 di Makassar - Syahdan Hidayat; Rahman Ambo Masse; Ayu Ruqayyah Yunus (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Along with people's desires that are increasingly complex in almost all aspects of life without being related to entertainment or musical performances but are limited to time and energy management, event organizers are an alternative that answers this, where event organizers are committees that work professionally with the aim of design, implement and be responsible for the implementation of these activities. The purpose of this study was to determine the mechanism of the cooperation contract at the event organizer project 13 with service tenants and related to the implementation of the ijarah contract in the cooperation contract agreement in the view of Islamic economics. The research method used is a qualitative method with a phenomenological approach, and the data collection methods used in this study are interviews and documentation. The results of this study showed that the project 13 system in which it complied with the applicable sharia provisions of the contract and there was a binding written cooperation contract, and based on the observations of the cooperation contract carried out by the event organizer project 13 included in the ijarah contract which in harmony and the terms are in accordance with the provisions of sharia. Key words: Ijarah, Event Organizer, Project 13